Representation of Islamic Marriage Rule on Javanese Novel Post-Reformation Era - Setyawan, Bagus Wahyu; Saddhono, Kundharu; Sulaksono, Djoko (UIN Maulana Malik Ibrahim Malang, 2020)
The focus in this research is to describe and explain the implementation of the rule of Islamic marriage on the modern Javanese novel post-reformation era. Data resources in this research are some of the Javanese novels published after 2000. This descriptive qualitative research used three phases of research: data reduction, data display, and conclusion drawing. The primary data resources were reduced and tested by using a triangulation technique to test data validity. Then, the result showed the examples of implementing the rule of Islamic marriage in Javanese novels of the post-reformation era. The author’s point of view influenced the plot and conflict of the rule of marriage in the story. Indirectly, a few examples of the rule of marriage in the Javanese novel of the post-reformation era can provide an illustration based on the Islamic sharia rule. The focus in this research is to describe and explain the implementation of the rule of Islamic marriage on the modern Javanese novel post-reformation era. Data resources in this research are some of the Javanese novels published after 2000. This descriptive qualitative research used three phases of research: data reduction, data display, and conclusion drawing. The primary data resources were reduced and tested by using a triangulation technique to test data validity. Then, the result showed the examples of implementing the rule of Islamic marriage in Javanese novels of the post-reformation era. The author’s point of view influenced the plot and conflict of the rule of marriage in the story. Indirectly, a few examples of the rule of marriage in the Javanese novel of the post-reformation era can provide an illustration based on the Islamic sharia rule. Fokus dalam penelitian ini adalah untuk mendeskripsikan dan menjelaskan mengenai penerapan hukum perkawinan islam dalam novel Jawa moden pascareformasi. Sumber data dalam penelitian ini adalah beberapa novel Jawa yang diterbitkan di atas tahun 2000. Penelitian ini berbentuk penelitian kualitatif deskriptif dengan tiga tahapan penelitian, yaitu reduksi data, sajian data, dan penarikan simpulan. Data-data dalam sumber data utama direduksi dan dianalisis dengan pembahasan masalah. Terakhir data-data yang diperoleh diuji dengan menggunakan teknik triangulasi untuk mendapat suatu derajat validitas data. Hasil dalam penelitian ini, ditemukan beberapa contoh penerapan hukum perkawinan Islam dalam novel Jawa pascareformasi. Hukum perkawinan yang disajikan dalam novel Jawa sesuai dengan alur dan konflik cerita yang dipengaruhi juga oleh sudut pandang pengarang. Secara tidak langsung, beberapa contoh penerapan hukum perkawinan dalam novel Jawa pascareformasi dapat memberikan gambaran masyarakat mengenai hukum perkawinan yang sesuai dengan syariat Islam dan yang menyimpang dari hukum syariat perkawinan islam.